Influence of ABCB1 and CYP3A5 gene polymorphisms on pharmacokinetics of apixaban in patients with atrial fibrillation and acute stroke - Kryukov AV; Sychev DA; Andreev DA; Ryzhikova KA; Grishina EA; Ryabova AV; Loskutnikov MA; Smirnov VV; Konova OD; Matsneva IA; Bochkov PO (Dove Medical Press, 2018)
Alexander Valerevich Kryukov,1 Dmitry Alekseevich Sychev,1 Denis Anatolevich Andreev,2 Kristina Anatolievna Ryzhikova,1 Elena Anatolievna Grishina,1 Anastasia Vladislavovna Ryabova,1 Mark Alekseevich Loskutnikov,3 Valeriy Valerevich Smirnov,4 Olga Dmitrievna Konova,1 Irina Andreevna Matsneva,2 Pavel Olegovich Bochkov1 1Russian Medical Academy of Continuous Professional Education, Moscow, Russia; 2Department of General Medicine, Sechenov First Moscow State Medical University, Moscow, Russia; 3L.A. Vorohobov City Clinical Hospital, Moscow, Russia; 4NRC Institute of Immunology FMBA of Russia, Moscow, Russia Introduction: Difficulties in non-vitamin K anticoagulant (NOAC) administration in acute stroke can be associated with changes in pharmacokinetic parameters of NOAC such as biotransformation, distribution, and excretion. Therefore, obtaining data on pharmacokinetics of NOAC and factors that affect it may help develop algorithms for personalized use of this drug class in patients with acute cardioembolic stroke. Patients and methods: Pharmacokinetics of apixaban in patients with acute stroke was studied earlier by Kryukov et al. The present study enrolled 17 patients with cardioembolic stroke, who received 5 mg of apixaban. In order to evaluate the pharmacokinetic parameters of apixaban, venous blood samples were collected before taking 5 mg of apixaban (point 0) and 1, 2, 3, 4, 10, and 12 hours after drug intake. Blood samples were centrifuged at 3000 rpm for 15 minutes. Separate plasma was aliquoted in Eppendorf tubes and frozen at -70°C until analysis. High-performance liquid chromatography mass spectrometry analysis was used to determine apixaban plasma concentration. Genotyping was performed by real-time polymerase chain reaction. CYP3A isoenzyme group activity was evaluated by determining urinary concentration of endogenous substrate of the enzyme and its metabolite (6-β-hydroxycortisol to cortisol ratio). Statistical analysis was performed using SPSS Statistics version 20.0. The protocol of this study was reviewed and approved by the ethics committee; patients or their representatives signed an informed consent. Results: ABCB1 (rs1045642 and rs4148738) gene polymorphisms do not affect the pharmacokinetics of apixaban as well as CYP3A5 (rs776746) gene polymorphisms. Apixaban pharmacokinetics in groups with different genotypes did not differ statistically significantly. Correlation analysis showed no statistically significant relationship between pharmacokinetic parameters of apixaban and the metabolic activity of CYP3A. Conclusion: Questions such as depending on genotyping results for apixaban dosing and implementation of express genotyping in clinical practice remain open for NOACs. Large population studies are required to clarify the clinical significance of genotyping for this drug class. Keywords: cardioembolic stroke, atrial fibrillation, non-vitamin K anticoagulants, apixaban, pharmacokinetics, pharmacogenetics